A Violent Threat to Conservation of Wetlands and the Existing Laws of Bangladesh: A Critical Analysis (Philosophy and Progress, 2016)
In Bangladesh, wetlands are nursing areas for fresh water species. The freshwater wetlands have been considered an inexhaustible source of its wealth, but are now overexploited and undervalued. Sound wetlands could contribute to a healthy and sustainable economic condition. The focal point of this article is to conserve natural resources with special attention to the freshwater wetlands. Even the ponds or reservoirs under the private ownership except certain circumstances would come within the term conservation of wetlands, though the personal rights and enjoyments are being hampered. Therefore, the wetlands should be utilized for welfare of the people by protecting those from ruination and preserving biodiversity through proper and time-befitting work plans. Moreover, the article contains a broad discussion of current laws regarding the conservation of wetlands. But very unfortunately, there is no specific provision of law for the sustainability of such wetlands, but to declare ecologically critical area while in a vulnerable situation.Philosophy and Progress, Vol#53-54; No#1-2; Jan-Dec 2013